Neem (Azadirachta indica) - Nature’s Drugstore - Rawat, G. S. (Indian Forester, 1995)
The Neem tree is one of the most important and valuable trees of India. The Non-Wood Products of Neem have multipurpose use in medicine, cosmetics and fertilizers. Neem oil and its derivatives are used in soap making and in Pharmaceutical Industry. Neem cake is good organic manure and is also used in the management of insect and pest. The present article is to highlight the uses of Non-Wood Products of neem in the daily life of majority of Indian population.